Compensation and Retention of Civil Servants in Uganda: A Case of Rubanda District Local Government. - Tubenawe, Akileo (Kabale University, 2023)
The purpose of this study was therefore investigating the effect of employee compensation on the retention of civil servants in Rubanda District Local Government. The study was guided by specific objectives, which include examining the effect of employee base salary on the retention of civil servants, examining the effect of employee mandatory benefits on the retention of civil servants, and analyzing the effect of performance incentives on the retention of civil servants in Rubanda District Local Government. This study used a cross-sectional survey research design utilizing both qualitative and quantitative data approaches. Using simple random and purposive sampling techniques, a total of 72 respondents were selected to participate in the study. Questionnaires, and interview guide methods of data collection were used in this study. On the impact of employee compensation on civil servants, the majority 100% of respondents agreed that their pay was low compared to the position they held; on receive overtime pay when they put in long hours, 23.6% of the respondents agreed with the assertion, compared to 76.4% of them who disagreed. There was a significant positive relationship between employee base salary and the retention of civil servants (p = < 0.01, rho= .648**) which suggested offering higher base salaries as an effective strategy for improving employee retention within the civil service. On the effect of employee mandatory benefits on the retention of civil servants, it was concluded that the majority 86.1% of the respondents disagreed that they were pleased with the level of leadership at their place of employment. The study found out a significant strong positive relationship between employee mandatory benefits and the retention of civil servants (p = < 0.01, rho= .756**) which suggests that by offering comprehensive benefits packages, organizations can enhance employee satisfaction, increase loyalty, and reduce turnover rates among civil servants. On the effect of performance incentives on the retention of civil servants, the majority 100% of the respondents agreed that they had been responsible for their activities at the district; 69.4% agreed that they had been respected to perform their activities; and 30.6% disagreed. Lastly, 93.1% of the respondents agreed that they used fellow workers to motivate others, compared to 6.9% of the respondents who disagreed with the statement during data collection. The study found that a significant and strong positive relationship existed between performance incentives and the retention of civil servants (p = < 0.01, rho .741**). It was recommended that staff base salaries be offered for efficient service delivery.